Algeria : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2011)
This paper assesses recent developments in gas markets and the implications for Algerian gas demand and prices. Algeria's gas production is stable but its share in global gas production has been on a downward trend since the early 2000s. The impact of a change in the spot oil price (WTI) on gas prices can be statically examined with a vector autoregression (VAR). The impact of spot oil prices on Algeria's contracted gas price remains strong, but export volumes are under pressure.